If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1x = 6 + -6 Combine like terms: 6x + -1x = 5x 5x = 6 + -6 Combine like terms: 6 + -6 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| 2i/3i | | 2w+2(1w+283)=19 | | 5p-95p+119p-p=151 | | 3[x+5]=27 | | 8x^2+10x+25= | | 2(3a+1)=5(a-1) | | 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 | | -7t+4=-10t-14 | | 4[m+4]=40 | | -7+4=-10+-14 | | 2x+50=110 | | 14x^4+92x-42x^2=0 | | 2x-3y+i(x-2y)=4-5i | | -4(7-5m+n)= | | 6+4b=2+5b | | -3=21m | | M+2M-2=0 | | 6(w+1)-(3-2w)=7w | | 3x2squared/12x6squared | | 9m+13=58 | | 3z+8-z=9+z-5 | | 6P+8Q-4=0 |